Merevitalisasi Tradisi: Mengadopsi Desa Adat di Bali sebagai Unit Perancangan Kota - T. Nirarta Samadhi (Antropologi Indonesia, 2003)
Urban design projects aim at achieving better environments in the sense that they are supportive of the culture of the inhabitants. Careful consideration of socio-cultural aspects of a space is a precursor to approach this goal. The existence of traditional settlements (i.e. desa adat) as spatio-cultural units in a Balinese setting has never been accommodated in the contemporary projects of urban spatial design. In this respect, the opportunity to achieve supportive environments is certainly become remote. Long known for the extensive traditional and religious role it has played in the life of the Balinese, the desa adat is central to that culture. Essentially, this unit is cosmologically independent and socio-religiously meaningful, and thus needs to be treated accordingly in a socio spatial manipulation process. With regard to the spatial design of the Balinese space, this cosmological unit (Geertz 1959, 1980) determines land use, street layout, location of settlement's elements, and the like (Parimin 1985; Samadhi 2001).This paper aims to explore the existence of desa adat as a Balinese cultural institution, and argues for its utilization as an urban design unit. Ultimately, it tries to promote multiculturalism and pluralism in the urban design as a socio-spatial process in the Indonesian planning system.